Development and validation of an HPLC method for tetracycline‐related USP monographs. (12th March 2014) - Hussien, Emad M.
ABSTRACT A novel reversed‐phase HPLC method was developed and validated for the assay of tetracycline hydrochloride and the limit of 4‐epianhydrotetracycline hydrochloride impurity in tetracycline hydrochloride commercial bulk and pharmaceutical products. The method employed L1 (3 µm, 150 × 4.6 mm) columns, a mobile phase of 0.1% phosphoric acid and acetonitrile at a flow rate of 1.0 mL/min, and detection at 280 nm. The separation was performed in HPLC gradient mode. Forced degradation studies showed that tetracycline eluted as a spectrally pure peak and was well resolved from its degradation products. The fast degradation of tetracycline hydrochloride and 4‐epianhydrotetracycline hydrochloride in solution was retarded by controlling the autosampler temperature at 4 °C and using 0.1% H3PO4 as diluent. The robustness of the method was tested starting with the maximum variations allowed in the US Pharmacopeia (USP) general chapter Chromatography <621>. The method was linear over the range 80–120% of the assay concentration (0.1 mg/mL) for tetracycline hydrochloride and 50–150% of the acceptance criteria specified in the individual USP monographs for 4‐epianhydrotetracycline hydrochloride. The limit of quantification for 4‐epianhydrotetracycline hydrochloride was 0.1 µg/mL, 20 times lower than the acceptance criteria. The method was specific, precise, accurate and robust. Copyright © 2014 John Wiley & Sons, Ltd.